STRATEGI PENGEMBANGAN USAHA HOTEL SYARIAH BATANG SIANOK MENURUT ETIKA BISNIS ISLAM - Ira Wahyuni Putri; Zuwardi (ADISAM PUBLISHER, 2023)
This study aims to identify and analyze the development strategy used by the Batang Sianok Syariah Hotel using SWOT analysis. This type of research uses qualitative data such as interviews, observations, and documentation which is carried out directly with the owners and employees of the Batang Sianok Syariah Hotel to obtain accurate, precise and real data. This study used 3 research informants such as interviews with the owner (owner), as well as hotel managers and hotel employees. In addition, the data obtained was also analyzed by the authors by applying SWOT analysis, IFE, EFE, SWOT Matrix, and Score Table. From this research it can be concluded that the Batang Sianok Syariah Hotel development strategy needs to take advantage of existing opportunities by minimizing the weaknesses possessed by the hotel. This strategy can be carried out by increasing promotional activities, cooperating with various agencies, improving products and services, adding existing facilities and improving the condition of hotel buildings, in this way it will be easier for hotels to attract potential customers.